"A kind of agonie in my thoughts": writing puritan and non-conformist women's pain in 17th-century England. Issue 2 (13th June 2018) - Searle, Alison
Abstract : The relationship between pain as a physical and emotional experience and the concept of suffering as an essential aspect of sanctification for faithful believers was a paradoxical and pressing theological and phenomenological issue for puritan and non-conformist communities in 17th-century England. Pain allows the paradox of non-conformists' valorisation and suppression of corporeality to be explored due to its simultaneous impact on the mind and body and its tendency to leak across boundaries separating an individual believer from other members of their family or faith community. The material world and the human body were celebrated as theatres for the display of God's glory through the doctrines of creation and providence despite the fall. Pain as a concept and experience captures this tension as it was represented and communicated in a range of literary genres written by and about puritan and non-conformist women including manuscript letters, spiritual journals, biographies and commonplace books. For such women, targeted by state authorities for transgressing gender norms and the religion established by law, making sense of the pain they experienced was both a personal devotional duty and a political act. Three case studies comprise a microhistory of 17th-century English puritan and non-conformist women's lived experience, interpretation and representation of pain, inscribed in a series of manuscripts designed to nurture the spiritual and political activism of their communities. This microhistory contributes to a better understanding of pain in early modern England through its excavation of the connections that such writers drew between the imperative to be visibly godly, their marginalised subject position as a proscribed religious minority and their interpretation of the pain they experienced as a result.